A Self-Calibration of Leaky VNA System for In-Fixture Measurements - Zbik, Mateusz; Wiatr, Wojciech (IEEE transactions on microwave theory and techniques, 2023)
We propose a new approach to calibrating four-port reciprocal test fixtures affected by leakage. It is based on the well-known 16-term error model that represents a stationary embedding of a two-port device tested. We determine all the terms from scattering matrices measured by a calibrated vector network analyzer (VNA) for just four symmetric standards (patterns), consecutively attached to the test ports. For the calibration, we employ three pairs of shorts, open circuits, and matched loads, and a reciprocal and symmetric transmitting pattern, the scattering parameters of which are unknown. We calculate the unknown parameters and error terms using a self-calibration algorithm and compact closed-form, analytical equations expressed in the scattering parameter notation. According to the abbreviated names of the employed patterns and the model, we call our procedure SOLR16 treating it as an extension of the popular short-open-load-reciprocal (SOLR) approach based on the eight-term error model for the leaky embedding. The SOLR16 method is particularly useful to calibrate test fixtures dedicated to mixed-mode device characterization as, e.g., leaky on-wafer probes. Experimental results of the calibration and in-fixture measurements of a photodetector encapsulated in a transistor outline (TO) package type confirm its efficacy and robustness.